Epileptic and cognitive changes in children with cerebral palsy: an Egyptian study - El-Tallawy HN (Dove Medical Press, 2014)
Hamdy N El-Tallawy, Wafaa MA Farghaly, Ghaydaa A Shehata, Reda Badry, Tarek A Rageh Department of Neurology, Assiut University Hospitals, Assiut, Egypt Background: Cerebral palsy (CP) is the most frequent cause of motor handicap among children. Aim of the study: We aim to study the relation of epilepsy in children with CP to various risk factors that affect the development of seizures. Patients and methods: In a cross-sectional, descriptive, population-based, case-control study, 98 children with CP (48 children with CP with epilepsy, and 50 children with CP without epilepsy) were compared with 180 children without CP or seizures. The children lived in two regions in Egypt: the Al-Kharga District–New Valley and El-Quseir city–Red Sea. These cases were subjected to meticulous neurological assessment, brain magnetic resonance imaging, electroencephalography, and Stanford-Binet (4th edition) examination. Multinomial logistic regression was used to assess the risk factors. Results: Epilepsy was diagnosed in 48.9% of all cases of CP. Mental subnormality was observed more frequently in children with epilepsy than in those without epilepsy (84.6% versus 66.7%). The frequency of epilepsy was highest in patients with the spastic quadriplegic type of illness (58.3%). Multinomial logistic regression revealed that prematurity (<32 weeks of pregnancy), low birth weight (<2.5 kg at birth), neonatal seizures, jaundice, and cyanosis were significantly associated with CP with epilepsy. Conclusion: CP is associated with a high percentage of seizure disorders. Prematurity, low birth weight, neonatal seizures, cyanosis, and jaundice are significant risk factors among patients with CP with epilepsy compared to patients with CP without epilepsy or a healthy control group. Keywords: cerebral palsy, epilepsy, risk factors, Egypt